Henbane (Hyoscyamus niger) poisonings in the vicinity of Erzurum - Kürkçüoğlu, Muzaffer (The Turkish Journal of Pediatrics, 1970)
In the region of Erzurum, in the spring, typical atropine poisoning is seen in children who eat the roots and leaves of henbane (Hyoscyamus niger) known here as "Deli Bat Bat". In this paper we have discussed 31 patients who were admitted to our hospital during the years 1966-1969. Within 24 hours the patients were out of danger from the intoxication and had shown improvement due to the use of only sufficient amounts of intravenous fluid to force diuresis. Apart from this, the use of Chlorothiazide was not found to be necessary. We are of the opinion that this diuretic is of use only if the patient has gone into a coma. All the patients that underwent treatment were discharged from hospital in good health.